Ultra high energy cosmic rays The intersection of the Cosmic and Energy Frontiers - Coleman, A.; Eser, J.; Mayotte, E.; Sarazin, F.; Schröder, Frank Gerhard; Soldin, D.; Venters, T.M.; Aloisio, R.; Alvarez Muñiz, J.; Alves Batista, R.; Bergman, D.; Bertaina, M.; et al. (Elsevier Science, 2023)
Fil: Coleman, A.. University of Delaware; Estados Unidos